Analgesic, Anti-inflammatory and Antidiarrheal Properties of Synthesized Benzimidazole Derivatives via In vivo and In silico Methods - Ananta, Mokaddas Flora; Saha, Poushali; Spriha, Sabiha Enam; Rahman, S M Abdur; Chowdhury, A K Azad (Dhaka University Journal of Pharmaceutical Sciences, 2024)
The present communication reports the pharmacological investigation of a few synthesized benzimidazole derivatives by in vivo and in silico approaches. The in vivo peripheral analgesic, central analgesic, anti-inflammatory and antidiarrheal potentialities of the synthesized analogs were examined in animal model. The peripheral analgesic experiment revealed noticeable effect for compounds 1 and 2 with writhing inhibition values of 79.66 and 83.05 %, respectively at a dose of 50 mg/kg in comparison with standard aceclofenac (85.59 % writhing inhibition at 25 mg/kg dose). After 60 minutes of oral administration, compounds 1 and 2 demonstrated higher tailflicking time of 2.96 ± 0.018 min and 2.83 ± 0.011 min at 50 mg/kg body weight dose compared to that of morphine (2.95 ± 0.13 min). Promising anti-inflammatory effects were observed for compounds 1 and 2 with 87.72 and 85.96 % paw edema inhibition in contrast to the standard aceclofenac showing 92.98 % reduction of rat paw edema. Concerning antidiarrheal proficiency, compounds 1 and 2 inhibited the frequency of defecation by 84.35 and 88.69 %, respectively at 50 mg/kg dose as compared to standard loperamide (85.22 % diarrheal inhibition at 25 mg/kg dose). Additionally, the synthesized analogs were subjected to molecular docking analysis against a variety of analgesic, anti-inflammatory and antidiarrheal target proteins namely cyclooxygenase-2, phospholipase A2, interleukin-1 receptor associated kinase-4 and μ-opioid receptor. Among the test compounds, 1 and 2 displayed outstanding binding affinities to all molecular targets which reconfirm their superior analgesic, anti-inflammatory and antidiarrheal attributes shown during in vivo analysis. Dhaka Univ. J. Pharm. Sci. 23(2): 157-169, 2024 (December)